Application of Stable Isotopes in Identifying the Sources and Formation of Sulfate and Nitrate in PM2.5: A Review - Jiamei Peng; Chen Cheng; Shanshan Wang; Gongren Hu; Jinpei Yan; Ruilian Yu (Atmosphere)
Sulfate and nitrate are important components of atmospheric PM2.5, which is the main contributor of haze. Therefore, studying the sources and formation mechanisms of atmospheric sulfate and nitrate is very important for the prevention and control of haze formation. Stable isotopes of sulfate and nitrate, including isotopic compositions of sulfur, oxygen, and nitrogen, can be comprehensively used to study the sources and formation pathways of sulfate and nitrate in PM2.5, and to evaluate the contribution of each source and each formation pathway. This paper briefly reviews the determination methods for sulfur, oxygen and nitrogen isotopes in sulfate and nitrate, focuses on the application of the above isotopes in identifying the sources and formation pathways of sulfate and nitrate in atmospheric PM2.5, and puts forward research prospects.